First-in-human study to assess the safety, tolerability, pharmacokinetics and immunogenicity of DS002, an anti-nerve growth factor monoclonal antibody - Ma, Tingting; Cao, Bei; Huang, Lei; Yang, Yuanxun; Geng, Yan; Xie, Pinhao; Zhao, Yu; Lin, Hui; Wang, Kun; Wang, Chunhe; Sun, Runbin; Li, Juan (Frontiers in Pharmacology, 2022)
Purpose: To evaluate the safety, tolerability, pharmacokinetics and immunogenicity of DS002 injection, an anti-nerve growth factor (anti-NGF) monoclonal antibody for treating pain conditions, in healthy Chinese subjects. Methods: This study was a single-center, randomized, double-blind, single-dose escalation, placebo-controlled design (CTR20210155). A total of 53 healthy subjects, 27 male and 26 female, were enrolled in this study, and one subject withdrew from the study before administration. Seven dose groups were set up, which were 0.5 mg, 1.0 mg, 2.0 mg, 4.0 mg, 7.0 mg, 12.0 mg and 20.0 mg, respectively. The drug was administered by single subcutaneous injection. Four subjects were enrolled in the first dose group (0.5 mg) received DS002. Other dose groups enrolled eight subjects each, six of whom received DS002 while the other two received a placebo. Safety, tolerability, pharmacokinetic parameters and immunogenicity of DS002 were assessed. Results: DS002 was well tolerated; all adverse events were Grade 1-2, and did not reach the termination standard of dose increment within the range of 0.5-20.0 mg. Adverse event rates were generally similar across treatments. After a single subcutaneous injection, the median Tmax in different dose groups ranged 167.77~337.38 h; mean t1/2 ranged 176.80~294.23 h, the volume of distribution (Vz) ranged 5265.42~7212.00 mL, and the clearance rate (CL) ranged 12.69~24.75 mL/h. In the dose range of 0.5~20.0 mg, Cmax ranged from 51.83±22.74 ng/mL to 2048.86±564.78 ng/mL , AUC0-t ranged from 20615.16±5698.28 h•ng/mL to 1669608.11±387246.36 h•ng/mL, and AUC0-inf ranged from 21852.45±5920.21 h•ng/mL to 1673504.66±389106.13 h•ng/mL. They all increased with dose escalation, and Cmax and AUC0-t did not have a significant dose-linear relationship, whilst AUC0-t was not dose-dependent at all. ADA test results of each group of all subjects in this trial were negative. Conclusion: DS002 showed satisfactory safety within the dose range of 0.5 mg to 20.0 mg. The absorption and metabolism of DS002 were slow, it exhibited a low volume of distribution and the clearance rate was low. These data suggest that DS002, by blocking nerve growth factor, is expected to become a novel, safe and non-addictive treatment for pain conditions.